2010
DOI: 10.1093/intimm/dxq062
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin tolerance attenuates airway allergic inflammation in model mice by suppression of the T-cell stimulatory effect of dendritic cells

Abstract: Prior exposure of dendritic cells (DCs) and monocytes/macrophages to LPS causes unresponsiveness to subsequent LPS stimulation, a phenomenon called endotoxin tolerance (ET). ET impairs antigen presentation of these cells to T cells by down-regulating expression of MHC class II and co-stimulatory molecules such as CD86 and CD40. Some epidemiological studies have shown that endotoxin acts as a protective factor for allergic diseases. Accordingly, LPS has beneficial effects on the onset of airway allergic inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…It is tempting to speculate that the impaired Ag-specific costimulatory capacity of CD11b + DC we observed in the draining LN of PS50G-treated mice (11) is due to a state of PS50G-induced DC refractoriness, possibly occurring due to induction of DC maturation in the absence of specific Ag uptake. An analogous situation occurs during endotoxin tolerance in which refractory or exhausted DC are induced following LPS stimulation, resulting in suppression of AAI (57,58). Overall, these data increase our understanding of how differently sized inert nontoxic particles differentially modulate pulmonary APC function and lung immune homeostasis.…”
Section: Discussionmentioning
confidence: 70%
“…It is tempting to speculate that the impaired Ag-specific costimulatory capacity of CD11b + DC we observed in the draining LN of PS50G-treated mice (11) is due to a state of PS50G-induced DC refractoriness, possibly occurring due to induction of DC maturation in the absence of specific Ag uptake. An analogous situation occurs during endotoxin tolerance in which refractory or exhausted DC are induced following LPS stimulation, resulting in suppression of AAI (57,58). Overall, these data increase our understanding of how differently sized inert nontoxic particles differentially modulate pulmonary APC function and lung immune homeostasis.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies reported that the functions of several types of immune cells were modified via TLR4-dependent stimulation (30,(36)(37)(38). We were unable to ascertain whether the clinical efficacy of UT12 was due to its effect on neutrophils alone or resulted from its action on multiple immune response systems.…”
Section: Figmentioning
confidence: 90%
“…LBP and sCD14 can be considered as relevant markers of endotoxins in plasma [36]. In this respect, given the long half-lives of sCD14 and LBP (24-48 h) compared with endotoxin (from <8 min in mice to a maximum of 3 hours in humans), sCD14 and plasma LBP seem to reflect long-term exposure to endotoxin rather than the measurement of endotoxemia itself [37,38], which is more reliable to measure transient kinetics of endotoxin absorption [4,30]. We thus advise to measure others markers as LBP and sCD14 to complete endotoxemia [33,39,40].…”
Section: Discussionmentioning
confidence: 99%